32Pi Labeled Transgenic Wheat Shows the Accumulation of Phosphatidylinositol 4,5-bisphosphate and Phosphatidic Acid Under Heat and Osmotic Stress - Annum, Nazish; Ahmed, Moddassir; Imtiaz, Khadija; Mansoor, Shahid; Tester, Mark; Saeed, Nasir A. (Frontiers in Plant Science, 2022)
The ensuing heat stress drastically affects wheat plant growth and development, consequently compromising its grain yield. As a primary sensor lipids act in the response pathway upon the perception of environmental cues. Phosphoinositide specific phospholipase C (PI-PLC) hydrolyzes Phosphatidylinositol 4,5-bisphosphate (PIP2) to generate Inositol 1,4,5 trisphosphate (IP3) and Diacylglycerol (DAG) which further phosphorylated into phosphatidic acid (PA) that acts as a second messenger and is involved in multiple processes, under stresses. In the current study, a Phospholipase C (PLC) signaling pathway was investigated in spring wheat (Triticum aestivum L) and evaluated its four AtPLC5 overexpressed (OE)/transgenic lines under heat and osmotic stresses through 32Pi radioactive labeling. Naturally, the wheat harbors only a small amount of PIP2. However, with the sudden increase in temperature (40ºC), PIP2 levels start to rise within 7.5 minutes in a time-dependent manner in wild type (Wt) wheat. While the Phosphatidic acid (PA) level also elevated up to 1.6-fold upon exposing wild type wheat to heat stress (40ºC). However, at the anthesis stage, a significant increase of ~4.5 folds in PIP2 level was observed within 30 minutes at 40ºC in AtPLC5 over-expressed wheat lines. Significant differences in PIP2 level were observed in Wt and AtPLC5-OE lines when treated with 1200 mM sorbitol solution. It is assumed that the phenomenon might be a result of the activation of PLC/DGK pathways. Together these results indicate that heat stress and osmotic stress activate several lipid responses in wild type and transgenic wheat and can explain heat and osmotic stress tolerance in wheat plant.